The expatriation of French research in sub-Saharan Africa: racial distinctions and scientific epistemologies (Senegal, Madagascar, Benin) - (:unkn) unknown (My University, 2019)
This article explores French social and academic practices in Africa via the Research Institute for Development. They reveal social mechanisms of isolation of French expatriate researchers in the host societies, economic and institutional hierarchies vis-à-vis their local counterparts, causing identity divisions between actors who maintain processes of racialization. These processes also appear in the scientific orientation of research programs and feed an academic asymmetry in favor of France vis-à-vis the African countries where its research is expatriated, despite many epistemological reflections.
Keywords: African Research